Profile of Obstetrics Fistula Clients; is the trend changing? (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess the changes in the profiles of obstetric fistula clients.Methods: This was a retrospective review of the medical records of all obstetric fistula clients managed by the Oyo state fistula team at University College Hospital and Adeoyo Maternity Hospital Ibadan, Nigeria.  A proforma was used to extract information on socio-demographic and obstetric characteristics of clients and was analyzed using SPSS 25.0. Level of significance was set at P